Students’ Perception Toward Oral Corrective Feedback in Speaking Classes: A Case at English Education Department Students - Muslem, Asnawi; Zulfikar, T.; Astilla, Inas; Heriansyah, Hendra; Marhaban, Saiful (Universitas Negeri Makassar, 2021)
The objective of this study was to investigate students’ perceptions towards oral corrective feedback from lecturers in their speaking classes. This survey involved 100 students of English Language Education Department, Ar-Raniry State Islamic University (UIN Ar-Raniry) Banda Aceh from 254 students. The participants of the survey were slected using a simple random sampling technique to represent all off the population. A modified questionnaire from Calsiyao (2015, p. 397) and Elsaghayer (2014, p. 77) was used to collect the data. The percentages were used to analyse the data collected from the questionnaires. The results showed that the students perceived lecturers’ oral corrective feedback as an important part of language learning. Lecturers’ oral corrective feedback was very helpful in improving the students’ speaking abilities. It can be concluded that oral corrective feedback gave positive results towards the students’ speaking performances. Therefore, this research was significant to highlight the students’ perceptions towards oral corrective feedback from their lecturers during the teaching and learning of speaking in their classes. Both lecturers and students would benefit from this research so that they can realize how important it is to give and accept oral corrective feedback.